Analisis Kelayakan Usaha Finansial Budidaya Melon Hidroponik di PT Indigen Karya Unggul - Putra, Zadika Winono; Setiadi, Agus; Setiyawan, Hery (Universitas Galuh, 2025)
Melons are one of the horticulture sub-sectors that have great potential to be marketed. However, in Yogyakarta melon production has decreased, considering this decline in production, an effective cultivation system is needed to increase melon productivity. Financial aspect analysis is also no less important in assessing the feasibility of PT Indigen Karya Unggul, considering that this analysis aims to avoid excessive use of capital or can be a consideration when wanting to build a new greenhouse for the sustainability of its hydroponic melon business which turns out to be less profitable. This research aims to determine the income and financial feasibility of the business at PT Indigen Karya Unggul. This research was conducted at PT Indigen Karya Unggul. This location was determined using a purposive method. The research method used is a case study. The analytical method used is analyzing income and financial feasibility criteria consisting of Net Present Value, Internal Rate of Return, Profitability Index, Payback Period, and Return on Investment. The research results show that the average income of the hydroponic melon business at PT Indigen Karya Unggul is IDR 143,900,889/year. The NPV value of the hydroponic melon business at PT Indigen Kara Unggul is IDR 146,5599,967, IRR is 10.61%, PI is 1.21, PP is for 3 years 4 months, and ROI is 20.54%. Based on these results, it can be concluded that the hydroponic melon business at PT Indigen Karya Unggul is profitable and feasible to run.